An improvement of employee performance by determining the employee’s job personality at Hawk Soon Hin Industry SDN BHD (HSH) - Oh, Hui Wen (2022)
Nowadays, having a better understanding of the employee job personality and their characteristics is a vital process especially for the employer or human resource manager in hiring, selecting and employing their employee. This can help to increase the employee's job performance at the same time to increase the productivity, effectiveness and efficiency of the company. Thus, the job personality of employees may be complex, inconsistent and unpredictable of the employer with different perceptions. One of the significant problems in this company is the low level of satisfaction, and a high number of employee turnovers. This action research will identify the issues related to employee personality and provide practical solutions to Hawk Soon Hin Industry Sdn Bhd (HSH) in order to build productive and satisfying employees and the workplace. To achieve that, this action research will identify the factor of employee personality characteristics that will affect the employee job performance. In addition, this research will determine the personality characteristics of an employee that will influence the employee job performance at HSH. This research had adopted the Big Five Model (OCEAN) as the conceptual theory that will guide the direction of the research. The practical importance of this study is to build up the reputation of this company by having a better understanding of their employee characteristics, perceptions, mindset and behaviour that can increase and maximize their job performance. The methodology choice of this research is used mixed-method which is the qualitative method and follows by quantitative method. The finding’s results of this action research will be important to all of the HR managers or every single employer by having a better understanding of the employee's characteristics and job personality. The potential of practicality is to know which types of employee's characteristics is the most influential towards the job performance.